Risk Factors of Pneumonia in Toddler at South Atambua Public Health Center and Halilulik Public Health Center - Tunabenani, Maria Rosdiana; Purnawan, Sigit; Landi, Soleman (Timorese Journal of Public Health, 2021)
Pneumonia is an acute disease that attacks the lung tissue (alveoli) and is caused by various microorganisms such as bacteria, viruses and fungi. Pneumonia is the main cause of death in children under five worldwide, this can be seen from almost every day around the world there are children under five who die from pneumonia. Apart from direct causes, pneumonia can also be caused by various risk factors such as low birth weight, immunization status, history of exclusive breastfeeding and smoking habits. The purpose of this study was to analyze the factors associated with the incidence of pneumonia in children under five at the Atambua Selatan Health Center and the Halilulik Health Center in 2020. This type of research was a quantitative analytic study using a case control method . The sample of this study amounted to 64 people consisting of a case sample of 32 toddlers and a control sample of 32 toddlers who were taken randomly. The research results were analyzed by univariate and bivariate using chi square test. Based on the results of the study, it was found that there was a significant relationship between low birth weight (p = 0.039), history of exclusive breastfeeding (p = 0.023) and smoking habits (p = 0.021) with the incidence of pneumonia in children under five, while for immunization status there was no relationship. significant (p = 1000) on the incidence of pneumonia in children under five. To avoid various health problems in toddlers, parents and health workers are expected to play an active role in paying attention to the health of toddlers so that toddlers can avoid various infectious diseases, especially pneumonia.